Pancreatic secretory trypsin inhibitor in gastrointestinal mucosa and gastric juice. Issue 11 (November 1990) - Freeman, T C; Playford, R J; Quinn, C; Beardshall, K; Poulter, L; Young, J; Calam, J
Abstract : We studied the distribution of pancreatic secretory trypsin inhibitor (PSTI) in the epithelia of the gastrointestinal tract and determined whether PSTI is secreted into gastric juice. PSTI was measured by a specific radioimmunoassay in biopsy specimens taken from the upper (n = 8) and lower (n = 7) gastrointestinal tract of patients with normal endoscopies. PSTI was present in the stomach, small intestine, and colon. Concentrations (micrograms/g protein) were highest in the stomach, and significantly higher in the antrum (1240, 670-1700, median and range) than in the gastric body (370, 350-570) (p less than 0.01). Concentrations were similar in the duodenum (180, 80-210) and colon (160, 130-360). PSTI determined by immunohistochemistry was present in mucus secreting gastric foveolar cells, duodenal Paneth cells, and colonic non mucus cells. PSTI was present in gastric juice. The median (range) concentration of PSTI in basal gastric juice from 13 patients with duodenal ulcers was 9 (3-21) micrograms/l and did not change during stimulation with pentagastrin. The rate of secretion, however, did increase significantly (p less than 0.05) from 1430 (180-2810) ng/h to 4500 (1250-12, 770) ng/h during pentagastrin stimulation. PSTI was labile in acid pepsin but stable in the neutral conditions present in the mucus layer. The presence of pancreatic secretory trypsin inhibitor throughout the gut and its secretion into the lumen suggests a hitherto unrecognised mechanism protecting gastrointestinal epithelia against luminal proteases.